(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Background: Incidence of detection of colorectal polyp is increasing in recent years. But factors associated with malignant potentiality of colorectal polyp is largely unknown. Aims of the study: The aim of this study was to correlate patient age and colonic polyp size with malignant potentiality. Materials and methods: This was an observational cross sectional study, carried out in Gastroenterology department of Combined Military Hospital (CMH) Dhaka cantonment in between January to December 2019. Total 240 patients were included in the study, whose underwent colonoscopy, had colonic polyps and polyp biopsy was done. Data was collected and analyzed by using SPSS 20 and obtained in tables and diagrams. Results: Out of 240 patients male 165(68.7%), female 75(31.3%) with male to female ratio 2.5:1; mean age±SD 53.3±15.4 years; below 40 years 43 (17.9%), 40-60 years 102 (42.5%) and above 60 years 95(39.6%); 92 (38.3%) patients had different co-morbidity including 39 (16.3%) had multiple co-morbidity; colonic polyps found in caecum 32(13.3%), ascending colon 14 (5.8%), transverse colon 8(3.3%), descending colon 20(8.3%), sigmoid colon 32(13.3%), rectum 104 (43.3%), and multiple sites 30(12.5%);180(75.0%) polyps were sessile and 60(25.0%) pedunculated with minimum size 3mm and maximum 21mm in diameter; polyps were of neoplastic 91(37.9%),hyperplastic 18 (7.5%), and inflammatory 131(54.6%); among neoplastic polyps 83(34.6%) benign and 8(3.3%) malignant; among neoplastic polyps mild dysplasia 66(72.5%), moderate dysplasia 17(18.7%) and severe dysplasia 8(8.8%); polyps larger than 10mm size were associated with increasing degree of dysplasia, odds ratio (OR) 9.2; 95% CI (2.9 to 29.1), p value < .001; patients of more than 60 years of age were also more associated with increasing degree of polyp dysplasia, odds ratio 3.5; 95% CI (1.3 to 9.2), p value .01. Conclusion: Increasing age of patients and increasing size of colorectal polyps were associated with increasing degree of dysplasia in colonic polyp histopathology. J Bangladesh Coll Phys Surg 2024; 42: 120-125